Adrenocortical tumours in children and adolescents: The EXPeRT/PARTNER diagnostic and therapeutic recommendations. (26th June 2021) - Virgone, Calogero; Roganovic, Jelena; Vorwerk, Peter; Redlich, Antje; Schneider, Dominik T.; Janic, Dragana; Bien, Ewa; López‐Almaraz, Ricardo; Godzinski, Jan; Osterlundh, Gustaf; Stachowicz‐Stencel, Teresa; Brugières, Laurence; et al.
Abstract: Adrenocortical tumours (ACTs) are rare during childhood. A complete surgical resection provides the best chance of cure, but the role and efficacy of the adjuvant therapy are still controversial. Various histologic criteria of malignancy for ACTs adopted in children do not facilitate comparative studies and are not completely shared. Therefore, a sharp demarcation between benign and malignant lesions has not been recognised, making it difficult to identify who potentially needs perioperative therapy. This manuscript presents the internationally harmonised recommendations for the diagnosis and treatment of ACTs in children and adolescents, established by the European Cooperative Study Group for Paediatric Rare Tumours (EXPeRT) group within the EU‐funded project PARTNER (Paediatric Rare Tumours Network ‐ European Registry).